Aspen shaving versus chip bedding: effects on breeding and behavior. (January 2015) - Jackson, E; Demarest, K; Eckert, W J; Cates-Gatto, C; Nadav, T; Cates, L N; Howard, H; Roberts, A J
The choice of laboratory cage bedding material is often based on both practical and husbandry issues, whereas behavioral outcomes rarely appear to be considered. It has been noted that a breeding success difference appears to be associated with the differential use of aspen chip and aspen shaving bedding in our facility; therefore, we sought to analyze breeding records maintained over a 20-month period. In fact, in all four mouse strains analyzed, shaving bedding was associated with a significant increase in average weanlings per litter relative to chip bedding. To determine whether these bedding types also resulted in differences in behaviors associated with wellbeing, we examined nest building, anxiety-like, depressive-like (or helpless-like), and social behavior in mice housed on chip versus shaving bedding. We found differences in the nests built, but no overall effect of bedding type on the other behaviors examined. Therefore, we argue that breeding success, perhaps especially in more challenging strains, is improved on shaving bedding and this is likely due to improved nest-building potential. For standard laboratory practices, however, these bedding types appear equivalent.